Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning (PBL) pada Kelas X.8 SMAN 2 Mataram - Batin, Siti Aminatin Ayunah; Amrullah; Ketut Wartana (Griya Journal of Mathematics Education and Application, 2025)
Efforts to improve student learning outcomes are one of the main goals in the education process, especially in mathematics subjects which are often considered challenging by most students. This study aims to improve student learning outcomes by implementing the Problem Based Learning (PBL) learning model. This study is a type of classroom action research and uses descriptive analysis. The subjects of the study were 40 students of class X-8 SMAN 2 Mataram in the 2024/2025 academic year. The research instrument used in this study was a test of student learning achievement using formative assessment. After the analysis, it was found that in cycle I the average score of students' mathematics learning outcomes was 76.18 with a classical completeness criterion of 67.50%. While in cycle II the average score of students' mathematics learning outcomes was 89.74 with a classical completeness criterion of 85.00%. Based on the results of this study, it shows that the application of the PBL learning model can improve mathematics learning achievement in the material on probability (distribution of probability) of class X-8 SMAN 2 Mataram.